Analysis of Students Problem Solving Skill from Online Worksheets with Integration of Video Demonstration - Irvani, Asep Irvan; Warliani, Resti; Fauziyyah, Salma Arfa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
This study aims to determine the profile of students’ problem solving skills using online worksheets with integration of physics demonstration videos. The demonstration video used comes from YouTube that open accessed. The method used is descriptive research method with research instruments in the form of online worksheets. The research was conducted at a university in arrowroot in the physics education department. The results showed that the students’ ability to focus on problems obtained 76% with high criteria. The score for the indicator describing the problem is 68% with high criteria. The score on the indicator of designing a problem solution is 64% with sufficient criteria. For indicators of doing problem solutions, a score of 52% with low criteria. In addition, for indicators of evaluating the results of the answers obtained a score of 49% with low criteria. The total average score obtained is 62%, which is sufficient. The results of this study can serve as an introductory source for research related to online worksheets and problem solving skills.